A forum theater corpus for discrimination awareness - Ochs, Magalie; Pergandi, Jean-Marie; Ghio, Alain; André, Carine; Sainton, Patrick; Ayad, Emmanuel; Boudin, Auriane; Bertrand, Roxane (Frontiers in Computer Science, 2023)
In this article, we present a new multimodal annotated corpus of forum theatre scenes on discrimination awareness. The collected interactions include scenes of ordinary sexism and racism situations playing by different actors in different contexts. The corpus also contains scenes of interactions between an author of a discriminatory behavior and a witness trying to make the discriminatory actor aware of their behavior. These confrontations scenes have been played considering different social attitudes (denial, aggressive, conciliatory). The experimental setup, including motion capture and audio-visual recordings, has been specifically designed to allow the semi-automatic annotation of the corpus and a fine-grained analysis of the multimodal cues associated to social behaviors.